Legal Due Diligence Perizinan Pemanfaatan Sumber Daya Air: Analisis Ketaatan Hukum, Risiko Bisnis, dan Strategi Mitigasi (Studi Kasus: Putusan No. 770/PID.SUS/2021/PN DPS-Usaha Cuci Mobil My Carwash, Denpasar, Bali) - Rachel Amanda Salwa; Angeline Christy; Naomi Margaretha; Winih Auraning; Zahra Shafarina (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This article analyzes the legal compliance aspects of water resource utilization licensing through a legal due diligence (LDD) approach based on a criminal case study. The object of study is the Denpasar District Court Decision Number 770/PID.SUS/2021/PN DPS, which adjudicated the case of unlicensed groundwater use by the My Carwash car wash business in Denpasar, Bali. This research employs a normative juridical method with statute and case approaches. Findings indicate that water resource licensing violations are categorized as highlevel legal risks that may result in criminal sanctions, business license revocation, and significant reputational damage. This article further formulates a comprehensive risk management framework and mitigation strategies for Limited Liability Companies utilizing water resources in their operational activities.